Mídias sociais digitais na administração pública municipal: uma análise do monitoramento na administração pública municipal - Salles, Ana Celina Quevedo (2023)
Technologies have revolutionized society and its way of life, there are countless examples of the influence of technology on society's daily routine. Currently, Digital Social Media are the preferred communication platforms, due to their ease of access and expression on any topic. In public organizations, its use aims to disseminate information and also social participation in relation to public actions. The objective of this research is to investigate the use of digital social media by Public Administration in the municipality of Santa Maria, in the State of Rio Grande do Sul. The study of this case has a descriptive purpose and uses content analysis to characterize the monitoring of Digital Social Media used (Facebook and Instagram) through semi-structured interviews with those responsible for the communication sectors, as well as observation of the sector's routine and analysis of publications on Digital Social Media. The interpretation of the material collected in the interviews was carried out through lexicographic analysis with the support of the IRaMuTeQ software. Based on a theoretical monitoring cycle, we analyzed the processes of publishing, monitoring and moderating Digital Social Media within the scope of Santa Maria City Hall. We found that a formalized management process is in place, but there is no formal monitoring. Furthermore, it was possible to systematize a structure to assist the process of providing and monitoring content in Digital Social Media in municipal management, which was compiled in the form of a guide. In this sense, we found that efficient monitoring of social media efficiently contributes to the growth of social networks at the municipal level, but the effects could be amplified with monitoring of social media carried out institutionally. This would allow for deeper reflection on the entire municipal management, based on data collected from Social Networks, as well as mediating institutional relationships in a way aimed at the target audience of the actions developed.